Needs Analysis: A Tool to Develop Specificity in English for Tourism Courses at Universidad Nacional, Brunca Branch - Segura Arias, Róger Alexánder (InterSedes, 2024)
Needs analysis plays a vital role in the development of English for Specific Purposes. However, in Costa Rica's tertiary education system, there is a scarcity of specific needs assessments aimed at curricular development. Therefore, the objective of this needs analysis is to propose a course for tourism students at Universidad Nacional, Brunca Branch. The analysis involved questionnaires and interviews conducted with alumni, current students, and potential employers from the Brunca region. The results revealed that employers are seeking individuals with English proficiency to assist tourists in various settings, such as hotels and travel agencies. Additionally, the assessment identified a specific need related to hotel reception, as it is the most common job position held by former students, making it a crucial task performed by this population. Based on the identified needs, two courses are suggested to address the students' requirements. Firstly, a general English for Occupational Purposes (EOP) course can be designed, focusing on common tourism topics such as Hotels, Travel Agencies, Transportation, and Airports. Secondly, a more specialized course, English for Hotel Reception, is recommended, which would cover areas such as customer service, English for telephone conversations, handling complaints, and other relevant skills.